(untitled) (Molecular Medicine Communications, 2023)
Cash incentives for COVID-19 vaccination involve offering individuals a financial reward as an encouragement to get vaccinated against the coronavirus. This strategy has been implemented by various governments, organizations, and businesses as part of their efforts to increase vaccination rates. Duch and colleagues randomly assigned about 700 residents of several villages in Ghana to four groups in a cluster-controlled trial. The results show that participants assigned to the cash incentive treatments had an average rate of 81% (1,733 of 2,168) compared to 71% (1,895 of 2,669) for those in the placebo treatment arm. For self-reported vaccinations, the average rate for participants in the cash treatment was 3.5% higher than for participants in the placebo treatment (95% confidence interval (CI): 0.001, 6.9; P = 0.045): 40% (602 of 1,486) versus 36.3% (672 of 1,850). These results suggest that cash incentives help in vaccination uptake but paradoxically, low cash incentives resulted in higher vaccine uptake compared to high cash incentives. We found that cash incentives motivate individuals who may be hesitant or reluctant to receive the COVID-19 vaccine. Financial rewards can serve as an additional motivator for those who may be on the fence about getting vaccinated. Trial identifier: AEARCTR-0008775. Nat Med. 2023 Nov 27. doi: 10.1038/s41591-023-02670-4.